Research Methods in Outdoor Studies, 1st edition - Humberstone, Barbara (Routledge, 2020)
Over the last two decades Outdoor Studies has emerged as an innovative and vibrant field of study. This is the first book to offer a comprehensive appraisal of established and cutting-edge research methods as applied to Outdoor Studies.